Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1369-1600.2009.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

PRECLINICAL STUDY: Route of administration affects the ability of naltrexone to reduce amphetamine‐potentiated brain stimulation reward in rats

Abstract: Opioid receptor antagonism has been shown to attenuate behavioral and neurochemical effects of amphetamine in humans and rodents. The effects of acute (oral or subcutaneous) or extended-release naltrexone (XR-NTX) were tested on the reward-enhancing effects of amphetamine using the intracranial self-stimulation (ICSS) paradigm. Acute exposure to drugs of abuse reduces the locus of rise (LOR) in the ICSS procedure, reflecting enhanced brain stimulation reward (BSR). Rats were treated once a day with naltrexone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…Furthermore, a randomized clinical trial of oral NTX (50 mg) for treating AMPH dependence demonstrated that treatment outcomes (number of AMPH-negative urine samples, rate of continuous abstinence, craving, and self-reported consumption of AMPH) were significantly improved in NTX compared with placebo-treated patients (N ¼ 40 per group; JayaramLindstrom et al, 2008a). Consistent with the clinical data, preclinical studies have demonstrated that NTX reduces the reinforcing effects of intravenous AMPH (Jimenez-Gomez et al, 2011), AMPH-induced decreases in the threshold for intracranial brain stimulation reward (Todtenkopf et al, 2009), and reinstatement of AMPH seeking (Haggkvist et al, 2009). The exact mechanism by which NTX altered AMPHinduced responses remains unclear.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, a randomized clinical trial of oral NTX (50 mg) for treating AMPH dependence demonstrated that treatment outcomes (number of AMPH-negative urine samples, rate of continuous abstinence, craving, and self-reported consumption of AMPH) were significantly improved in NTX compared with placebo-treated patients (N ¼ 40 per group; JayaramLindstrom et al, 2008a). Consistent with the clinical data, preclinical studies have demonstrated that NTX reduces the reinforcing effects of intravenous AMPH (Jimenez-Gomez et al, 2011), AMPH-induced decreases in the threshold for intracranial brain stimulation reward (Todtenkopf et al, 2009), and reinstatement of AMPH seeking (Haggkvist et al, 2009). The exact mechanism by which NTX altered AMPHinduced responses remains unclear.…”
Section: Introductionmentioning
confidence: 84%
“…Beginning approximately 6-7 days after surgery, rats were trained on a continuous reinforcement schedule (FR1) to respond for rewarding brain stimulation in operant chambers interfaced with stimulators (Med Associates, St. Albans, VT) as previously described (Todtenkopf et al, 2009). Using customized software, each lever-press earned a 0.5-s train of square-wave cathodal pulses (0.1-ms pulse duration) at a set frequency (178 Hz).…”
Section: Icss Proceduresmentioning
confidence: 99%
“…To confirm electrode placements, rats were perfused with 4% paraformaldehyde and sections through the lateral hypothalamus were stained with cresyl violet as previously described (Todtenkopf et al, 2009). …”
Section: Histologymentioning
confidence: 99%
See 2 more Smart Citations